2017
DOI: 10.1371/journal.pone.0185959
|View full text |Cite
|
Sign up to set email alerts
|

Sieve analysis of breakthrough HIV-1 sequences in HVTN 505 identifies vaccine pressure targeting the CD4 binding site of Env-gp120

Abstract: Although the HVTN 505 DNA/recombinant adenovirus type 5 vector HIV-1 vaccine trial showed no overall efficacy, analysis of breakthrough HIV-1 sequences in participants can help determine whether vaccine-induced immune responses impacted viruses that caused infection. We analyzed 480 HIV-1 genomes sampled from 27 vaccine and 20 placebo recipients and found that intra-host HIV-1 diversity was significantly lower in vaccine recipients (P ≤ 0.04, Q-values ≤ 0.09) in Gag, Pol, Vif and envelope glycoprotein gp120 (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
2
27
1
Order By: Relevance
“…The case-only method (65) was employed to assess whether and how each Fc␥R SNP modified the vaccine/placebo hazard ratio of HIV-1 acquisition risk (HR) between week 28 and month 24. The case-only method was also used to assess whether and how each Fc␥R SNP modified the hazard ratio of Env sequence-specific HIV-1 acquisition risk studied in the sieve analysis (13).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The case-only method (65) was employed to assess whether and how each Fc␥R SNP modified the vaccine/placebo hazard ratio of HIV-1 acquisition risk (HR) between week 28 and month 24. The case-only method was also used to assess whether and how each Fc␥R SNP modified the hazard ratio of Env sequence-specific HIV-1 acquisition risk studied in the sieve analysis (13).…”
Section: Methodsmentioning
confidence: 99%
“…While this trial was unblinded early due to lack of overall VE, recent studies identified several correlates of HIV-1 acquisition risk in HVTN 505, including Env-specific CD8 ϩ T-cell response magnitude and polyfunctionality score (PFS) (11), Env-specific humoral IgG responses (12) and antibody Fc effector functions (antibody-dependent cellular phagocytosis [ADCP] and Fc␥RIIa binding) (76). Moreover, the vaccine/placebo hazard ratio of HIV-1 acquisition significantly varied by the type of HIV-1 virus, defined by amino acid sequence distance of the HIV-1 CD4 binding site to the vaccine insert sequence, a "sieve effect" (13). Cumulatively, these findings suggest that the DNA/rAd5 vaccine regimen has had differential effects on HIV-1 acquisition depending on immunologic and virologic markers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There was no effect of the vaccine on acquisition of HIV-1 infection. However, the vaccine left a footprint of immune pressure on the Env protein of breakthrough variants (8). Further, it elicited a high rate of antibody-dependent cellular phagocytosis (ADCP) with a broad dynamic range (8).…”
Section: Antibody Fc Interactions Correlated With Reduced Hiv-1 Acquimentioning
confidence: 99%
“…However, the vaccine left a footprint of immune pressure on the Env protein of breakthrough variants (8). Further, it elicited a high rate of antibody-dependent cellular phagocytosis (ADCP) with a broad dynamic range (8). To identify immune risk correlates, the authors used a case-control strategy in which they compared immune measures between 125 uninfected and 25 infected vaccine recipients, sampled at 4 weeks after the final rAd5 immunization (6).…”
Section: Antibody Fc Interactions Correlated With Reduced Hiv-1 Acquimentioning
confidence: 99%